Literature Review: The Correlation Between Family Support and Preeclampsia Prevention Behavior - Roikah, Desi; Ani, Lisa Fitri; Maryati, Sri; susanti; Mawardika, Tina (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Preeclampsia is one of the most serious pregnancy complications and contributes significantly to maternal and fetal mortality. The prevention of preeclampsia can be achieved through regular antenatal care (ANC) examinations and early detection of risk factors during pregnancy. Family support, especially from husbands, plays an important role in improving pregnant women’s compliance with ANC visits and preeclampsia prevention behaviors. This study aimed to analyze the correlation between family support and preeclampsia prevention behavior among pregnant women based on previous research findings. The study employed a literature review method using research articles obtained from Google Scholar published between 2017 and 2025 with the keywords “preeclampsia,” “ANC compliance,” and “family support.” Of the 60 articles identified, 10 articles met the inclusion criteria and were considered relevant to the objectives of the study. The findings showed that family support was significantly associated with early detection behavior of preeclampsia risk, ANC compliance, pregnancy care behavior, and the psychological condition of pregnant women with preeclampsia. Pregnant women who received good family support were more likely to attend ANC visits regularly, comply with healthcare recommendations, and experience lower levels of anxiety. In conclusion, family support plays an important role in efforts to prevent preeclampsia. Therefore, families and healthcare providers are expected to enhance their involvement and provide continuous education to pregnant women in order to prevent pregnancy complications at an early stage